Ekonomi Islam di Mata Ekonom Non-Muslim: Telaah Pemikiran John R. Presley - Ubaidillah, Ahmad (Universitas Islam Lamongan, 2025)
This paper aims to examine Islamic economic thought from non-Muslim economist, John R. Presley. This research is a library research, which is a research process that reviews literature and analyzes relevant topics. In collecting data, the author utilizes journals, books, dictionaries, magazines, and other library sources. The analytical method used in this study is the hermeneutic method, which is interpreting, explaining, interpreting, and translating these data sources. The results of the study indicate that Islamic economics, according to Presley, can be a useful field of dialogue between the Islamic world and the West. A broader appreciation of Islamic economics will not only increase the Western world's understanding of how the Muslim economy operates, but also offer an interesting perspective on many Western economic principles. In addition, according to Presley, Islamic financial institutions, especially Islamic banks, as interest-free finance have developed surprisingly far. Interest-free banks have proven to be durable and enjoy substantial deposit growth. The impact of non-interest operationalization on the determination of foreign exchange rates and international capital flows, and the proper accounting definition of `profit' to be shared with suppliers of capital are some of the serious issues that, according to Presley, practitioners and theorists of Islamic financial institutions must face.